2019
DOI: 10.1111/dom.13626
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind, randomized clinical trial assessing the efficacy and safety of early initiation of sitagliptin during metformin uptitration in the treatment of patients with type 2 diabetes: The CompoSIT‐M study

Abstract: Aims To characterize the glycaemic efficacy and safety of initiation of the dipeptidyl peptidase‐4 inhibitor sitagliptin during metformin dose escalation in people with type 2 diabetes (T2D) not at glycated haemoglobin (HbA1c) goal on a sub‐maximal dose of metformin. Materials and methods Study participants with HbA1c ≥58 mmol/mol and ≤97 mmol/mol (≥7.5% and ≤11.0%) while on 1000 mg/d metformin were randomized to sitagliptin 100 mg once daily or placebo. All were to upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Three smaller studies compared increments in metformin dosing from 1,000 to 2,000 mg/day to continuation of metformin 1,000 mg/day with additions of sitagliptin (20), vildagliptin (21), or rosiglitazone (22). Respectively, for participants whose metformin dose was increased, these studies showed changes in HbA 1c of 20.80% (28.7 mmol/mol) from a baseline mean of 8.7% (72 mmol/mol), 20.37% (24.0 mmol/mol) from a baseline mean of 7.3% (56 mmol/mol), and 20.71% (27.8 mmol/mol) from a baseline mean of 8.0% (64 mmol/mol).…”
Section: Discussionmentioning
confidence: 99%
“…Three smaller studies compared increments in metformin dosing from 1,000 to 2,000 mg/day to continuation of metformin 1,000 mg/day with additions of sitagliptin (20), vildagliptin (21), or rosiglitazone (22). Respectively, for participants whose metformin dose was increased, these studies showed changes in HbA 1c of 20.80% (28.7 mmol/mol) from a baseline mean of 8.7% (72 mmol/mol), 20.37% (24.0 mmol/mol) from a baseline mean of 7.3% (56 mmol/mol), and 20.71% (27.8 mmol/mol) from a baseline mean of 8.0% (64 mmol/mol).…”
Section: Discussionmentioning
confidence: 99%
“…There are additional reports on DDIs between metformin and clinical used drugs. Frias et al reported that in subjects who did not reach the maximal goal of HbA1c with a sub-maximal dose of metformin, the addition of sitagliptin improved the glycemic response and glycated hemoglobin goals, while the safety and tolerability were similar with metformin treatment alone ( Frias et al, 2019 ). A possible mechanism is that the inhibition of OCT1 by sitagliptin could reduce the phosphorylation of AMPK, the first step in metformin's action ( Choi et al, 2010 ).…”
Section: Interaction Of Organic Cation Transporter 1 With Clinical mentioning
confidence: 99%
“…Metformin, as its pharmacological cotherapeutic actions, also stabilises the HbA1c levels, along with reduction in weight, among these patients affected with diabetes associated obesity. [3][4][5][6][7][8][9][10][11][12][13][14][15] Several systematic reviews had been conducted on various oral hypoglycaemic drugs, including metformin. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] To further supplement these systematic reviews, with the main objective to understand and illuminate on the perspectives of metformin rational pharmacotherapeutics, this systematic review was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15] Several systematic reviews had been conducted on various oral hypoglycaemic drugs, including metformin. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] To further supplement these systematic reviews, with the main objective to understand and illuminate on the perspectives of metformin rational pharmacotherapeutics, this systematic review was conducted. This systematic review of the different and wide-ranged studies on metformin rational pharmacotherapeutics was performed, for a better, clear and complete comprehension of multi-centre maintenance of rational pharmacotherapeutic aspects in regular anti-diabetic treatments prescribed to the new type II diabetic patients.…”
Section: Introductionmentioning
confidence: 99%